Empirical Studies on Property and Real Estate Sector Companies Listed on the Indonesian Stock Exchange for the Period 2019–2022: Determining the Accuracy of Financial Reporting - Ridho Nugroho, Tatas (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The objective of this study is to examine the impact of firm size, profitability, leverage, and institutional ownership on the promptness of financial reporting. This study employs secondary data sourced from real estate businesses that are publicly listed on the Indonesian Stock Exchange over the period spanning from 2019 to 2022. The study collected a total of 52 annual financial reports from 13 organizations between the years 2019 and 2022, using selective sampling. The present study employed logistic regression analysis with the aid of the Statistical Package for the Social Sciences (SPSS) software to analyze the data. The findings of the study indicated that there was no significant impact of firm size, profitability, and institutional ownership on the veracity of financial reporting.